Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


G(x) = 3/x-1
first step,    let g(x) = y
thus        y= 3/x-1
2nd step interchange      x for y  & y for x
     x= 3/y-1
3rd step      solve for y in term of x
x(y-1)= 3
y =    3/x +1
therefore the inverse function is
       f⁻¹(x) =    3/x +1

0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts